Let . Find .
make its y=15x^3-3
y+3=15x^3
I think up to this point I am right,
My final answer is this y= but its wrong
When finding an inverse function, the x and y values swap. So if $\displaystyle \displaystyle \begin{align*} f(x) \end{align*}$ is given by $\displaystyle \displaystyle \begin{align*} y = 15x^3 - 3 \end{align*}$ then $\displaystyle \displaystyle \begin{align*} f^{-1}(x) \end{align*}$ will be defined by
$\displaystyle \displaystyle \begin{align*} x &= 15y^3 - 3 \\ x+3 &= 15y^3 \\ \frac{x + 3}{15} &= y^3 \\ \sqrt[3]{\frac{x + 3}{15}} &= y \end{align*}$
So the inverse function is $\displaystyle \displaystyle \begin{align*} f^{-1}(x) = \sqrt[3]{\frac{x + 3}{15}} \end{align*}$